Chromoendoscopy with particular reference to a modified endoscopic Congo red test - Toth, Ervin (Ervin Tóth, Department of Medicine, Malmö University Hospital, 205 02 Malmö, Sweden, 2002)
Chromoendoscopy, endoscopic tissue staining, is an adjunctive method using chemical agents applied to the mucosal surface in order to aid gastrointestinal endoscopic diagnosis and therapy. Acid producing mucosa in the GI tract may be visualized endoscopically by Congo red staining in combination with stimulation of gastric acid production. Congo red is a reactive indicator dye that changes color from red to dark blue/black at a pH of less than three. We have modified the conventional Congo red test, and characterized a rapid approach, modified endoscopic Congo red test (MCRT). In this test, within five minutes after pentagastrin injection, the Congo red coated normal, acid producing fundal mucosa turns to a blue/black color. The two shortcomings in the original method, the time of dose-response and the dose of acid stimulant pentagastrin, are circumvented by our modification. The dose-response delay was reduced by 63% from 10-20 minutes to around five minutes, and the dose/kg of pentagastrin by 30 times, giving it intravenously instead of intra-muscularly. MCRT was applied in 589 examinations in order to study gastric mucosa in subjects with both non-operated and resected stomachs. MCRT was found to be a rapid, inexpensive and well-tolerated method to visualize acid producing mucosa during routine gastroscopic examination. MCRT increases the diagnostic accuracy of routine gastroscopy in detecting chronic atrophic fundal gastritis (sensitivity from 0.25 to 1.0 and specificity from 0.88 to 0.95, respectively). This is a rapid and accurate method (accuracy 0.98) to detect hypo/achlorhydria during gastroscopic examination. Morphological and functional information provided by MCRT may influence the clinical managements of patients. Future outcome studies should more precisely define the potential indications and the clinical benefit of MCRT.
Article: I. Tóth E, Sjölund K, Thorlacius H. Modified endoscopic Congo red test: a rapid chromo-endoscopic method to visualize gastric acid secretion compared with conventional Congo red test.Digestive Endoscopy 2002; Submitted for publication. Article: II. Tóth E, Sjölund K, Fork FT, Lindström C. Chronic atrophic fundic gastritis diagnosed by a modified Congo red test.Endoscopy 1995; 27: 654-658. Article: III. Tóth E, Sjölund K, Thorsson O, Thorlacius H. Evaluation of gastric acid secretion by use of modified endoscopic Congo red test. Gastrointestinal Endoscopy 2002; Accepted for publication. Article: IV. Tóth E, Sjölund K, Thorlacius H. Chromoendoscopic evaluation of gastricmucosa after partial gastrectomy by use of modified Congo red test.World Journal of Surgery 2002; Submitted for publication.
Keywords: Gastroenterologi; Gastro-enterology; therapy; diagnosis; gastrointestinal endoscopy; Chromoendoscopy; Congo red